Density and Dispersal Radius of Tamarixia radiata for Control of Diaphorina citri in Citrus Groves - Marin, Denis Rogério; Eduardo, Wellington Ivo; Diniz, Alexandre José Ferreira [UNESP]; Miranda, Marcelo Pedreira; Zanardi, Odimar Zanuzo; Tomaseto, Arthur Fernando; Garcia, Adriano Gomes; Parra, José Roberto Postali; Volpe, Haroldo Xavier Linhares (Springer Nature, 2023)
Tamarixia radiata (Waterston) is the main parasitoid wasp released in abandoned, organic, and non-commercial citrus groves and in orange jasmine areas for biological control of Diaphorina citri Kuwayama (a vector of bacteria associated with huanglongbing), as a control tactic in a strategy termed External Management. The effectiveness of parasitism is influenced by the release density and radius of action of this parasitoid. This study determined the optimal release density and radius of action of T. radiata in a commercial citrus grove. Parasitoids were released at five densities (200, 400, 800, 1,600, and 3,200 wasps/ha) at the center of circular areas with four different radii (7.5, 15, 22.5, and 30 m). The parasitism rate was assessed using ‘Valencia’ sweet orange seedlings, each bearing 35 D. citri fourth-instar nymphs, attached to 26-year-old ‘Valencia’ sweet orange trees along the perimeter of each radius. For the 7.5-m radius, the highest parasitism rate (74.1%) was observed at the density of 3,200 wasps/ha. However, for the 15-m radius, the density of 3,200 wasps/ha resulted in lower parasitism (30.7%) of D. citri nymphs. No parasitism was observed for densities lower than 800 wasps/ha and release radii above 15 m. The highest parasitoid dispersal radius and area were 18.04 m and 114.02 m2, respectively, when 3,200 wasps were released. Therefore, 3,200 wasps/ha arranged at 56 equidistant release points (approximately 57 wasps/release point) is the recommended protocol for biological control of D. citri in citrus groves.
Keywords: Asian citrus psyllid; Biological control; Huanglongbing management; Parasitism; Parasitoid dispersal; Parasitoid wasp release method